Cytogenetics Past, Present and Further Perspectives - Larramendy, Marcelo; Soloneski, Sonia (IntechOpen, 2019)
Cytogenetics - Past, Present, and Further Perspectives discusses events that influenced the development of cytogenetics as a specialty within biology, with special attention paid to methodological achievements developed worldwide that have driven the field forward. Improvements to the resolution of chromosome analysis followed closely the introduction of innovative analytical technologies. In that sense, this book reviews and provides a brief account of the structure of chromosomes and stresses the high structural conservation in different species with an emphasis on aspects that require further research. However, it should be kept in mind that the future of cytogenetics will likely depend on improved knowledge of chromosome structure and function.